Exploration of conceptions and attitudes of chemical engineers from Bogotá and Manizales about chemical engineering (2018)
"Background and purpose: It is expected to identify and compare the structure and genesis of the conceptions and attitudes of students of chemical engineering and chemical engineers graduated from Bogotá and Manizales, on chemical engineering, based on their sociocultural differences. In Colombia, the perception of chemical engineers about themselves and chemical engineering seems to be related to the utility that this profession has for the economic development of the country and to solve industrial problems and challenges. This suggests that this perception is very appreciated by this community and for the universities that teach this discipline because these are skills to get a job. However, this perception of chemical engineering seems to be different depending on the territory. Methodology: A questionnaire of closed and open questions was applied, by snowball, to students and graduates of chemical engineering from the universities of Bogotá and Manizales. For more in-depth information, semi-structured interviews were conducted with a smaller population..."--Tomado del Formato de Documento de Grado.